Role of Percutaneous Laser Disc Decompression in Patients with Lumbar Disc Herniation on Pain Relief: A Quasi-Experimental Pilot Study: - Boustani, Mohammad Reza; Saghebdoust, Sajjad; Shafagh, Seyed Ghavam; Pak, Neda; Fekrazad, Reza; Khadivi, Masoud; Faghih Jouibari, Morteza (Galen Medical Journal, 2022)
Background: Disc herniation is broadly deï¬ned as a localized or focal displacement of disc material beyond the limits of the intervertebral disc space. The disc material may be the nucleus, cartilage, fragmented apophyseal bone, annular tissue, or any combination thereof. Laser surgery is one of the treatment modalities for treating patients with lumbar disc herniation. This study aims to examine the effect of Percutaneous Laser Disc Decompression (PLDD) in patients with lumbar disc herniation. Materials and Methods: This study was conducted on 58 patients who underwent PLDD (optical fiber inserted through an 18G needle, 8 joules, and 8 watts). Individuals were monitored before and after treatment using the comparing visual analog scale (VAS) pain score (from 0 [no pain] to 10 [severe pain]). Results: The mean age of participants was 63.19Â±13.48 years. Regarding gender, 24 patients (41.4%) were female. The mean VAS score before surgery was 8.73Â±1.29, and VAS score after surgery was 55.2Â±2.71, which means pain was significantly reduced (P<0.001). Conclusion: The patientsâ€™ post-PLDD pain may decrease; hence, PLDD can use as an appropriate method for treating lumbar disc herniation. [GMJ.2022;11:e2382]